Wendelstein 7-X Magnets: Experiences Gained During the First Years of Operation. (17th November 2019) - Rummel, Thomas; Riße, Konrad; Nagel, Michael; Mönnich, Thomas; Schneider, Matthias; Füllenbach, Frank; Bosch, Hans-Stephan; ,
Abstract: The Wendelstein 7-X (W7-X) experimental fusion device went into operation in 2015 after intensive commissioning. Meanwhile, the third plasma operation phase started and ran until October 2018. W7-X has three magnet systems. The superconducting magnet system creates the main magnetic field of W7-X. It consists of 70 superconducting coils, divided into seven individual circuits with ten coils each. Seven equal power supplies provide the electrical current to power the magnets. Seven magnet protection systems are also part of the system. A magnet protection system allows fast discharge of the magnets in case of severe failures, e.g., a quench that means a sudden transition from the superconducting to the normal conducting state. A special sensor system, the quench detection system, checks the status of the magnets continuously. During each of the operation phases, the superconducting magnet system is kept under cryogenic conditions at about 4 K. For that, a helium refrigerator with total power of 7 kW at 4.5 K runs steady state 24/7. The second magnet system is the trim coil system, a set of five copper coils, placed at the outer side of the machine cryostat. The coils are powered by five identical power supplies. The third magnet system is the control coil system, a set of ten copper coils, placed inside of the plasma vessel behind the divertor targets. Ten 4-quadrant power supplies power each coil separately. The power supplies can deliver bidirectional direct currents and, as per request by the experimental program, an alternating current with adjustable frequencies between 1 and 20 Hz. An operation phase of W7-X comprises about 20 weeks. During the phase, the magnet systems are normally operated 2 or 3 days per week. The superconducting magnet system is usually switched on in the morning, kept energized during the day, and ramped down in the evening. This paper analyzes the operation phases, reports on the issues during the operation, and names countermeasures and improvements performed during the breaks between the operation phases.